The Impacts of Different Expansion Modes on Performance of Small Solar Energy Firms: Perspectives of Absorptive Capacity - Hsing Hung Chen; Tao Shen; Xin-long Xu; Chao Ma (The Scientific World Journal)
The characteristics of firm’s expansion by differentiated products and diversified products are quite different. However, the study employing absorptive capacity to examine the impacts of different modes of expansion on performance of small solar energy firms has never been discussed before. Then, a conceptual model to analyze the tension between strategies and corporate performance is proposed to filling the vacancy. After practical investigation, the results show that stronger organizational institutions help small solar energy firms expanded by differentiated products increase consistency between strategies and corporate performance; oppositely, stronger working attitudes with weak management controls help small solar energy firms expanded by diversified products reduce variance between strategies and corporate performance.